Decay of historic azulejos in Portugal: an assessment of research needs - Mimoso, J. (2009)
The communication is an overview of a recent investigation on the decay of azulejos that included field work, laboratory observations and numerical simulations aimed at the identification of forms of decay and assessing research needs in the field.